Exchange‐Rate Risk and Japanese–Thai Industry Trade1. (27th May 2015) - Bahmani‐Oskooee, Mohsen; Hegerty, Scott W.; Satawatananon, Kaveepot
Abstract : Over the past decade, many papers have studied the effects of exchange‐rate volatility on international trade, particularly at the bilateral level for large numbers of individual industries. This is necessary because the underlying theory is ambiguous and because earlier papers failed to uncover significant results at a higher degree of aggregation. This paper examines the case of Japan and Thailand over the period from 1970 to 2010. We find that slightly more than half of 117 export industries and 54 import industries are affected by volatility in the short run. In the long run, 6 export and 2 import industries are affected positively, and 22 export and 9 import industries are affected negatively. Small Japanese export industries are more likely to be negatively affected, while imports show no differences regarding industry size. In a sectoral analysis, we find some evidence that Japanese exports of manufactures and certain machinery and transport equipment might be relatively more affected by the exchange‐rate risk. Raw material imports are least affected. These findings therefore suggest which industries might benefit most by a policy promoting a stable yen.